Formulasi Cookies Motin Berbasis Mocaf-Patin sebagai Alternatif Pangan Darurat Sumber Protein bagi Ibu Hamil - Elysia, Syahda; Hastuti, Widi; Rahmat, Mamat; Sulaeman, Agus (Jurnal Gizi dan Dietetik, 2025)
Limited post-disaster food access emphasizes the importance of providing nutritious and easily consumed emergency food for all age groups, especially vulnerable pregnant women. Cookies, a potential emergency food, are formulated from highly nutritious local ingredients such as mocaf (Modified Cassava Flour), catfish flour (Pangasius sp.). This study aims to determine the effect of mocaf and patin fish flour formulations on the quality and nutritional value of Motin Cookies as an alternative emergency food for pregnant women. The research design was a one-factor CRD experimental study with mocaf and patin fish flour formulation formulations F1 (80%:20%), F2 (70%:30%), and F3 (55%:45%). The research method used a hedonic test to determine the organoleptic properties, calculation method to determine energy and carbohydrate content, titrimetry to determine protein content, gravimetry to determine fat content, ICP-OES to determine iron (Fe) content, and UV-Vis spectrophotometer to determine antioxidant activity values. The results of the study concluded that there were no significant differences in the hedonic test on the aspects of color, aroma, taste, texture and overall. Cookies with a 55%:45% formula have better acceptance than other formulas. The nutritional value of Motin Cookies per serving (50 grams) is 218.82 kcal of energy, 8.76 grams of protein, 8.81 grams of fat, 26.11 grams of carbohydrates, and 2.04 mg of iron. The antioxidant activity of Motin Cookies IC50 of 1325.79 mg/L is categorized as a very weak antioxidant. Further research is needed regarding the intervention of providing Motin Cookies as an alternative emergency food for pregnant women.